2011
DOI: 10.1007/s00198-010-1521-x
|View full text |Cite
|
Sign up to set email alerts
|

A review of patient-centred post-fracture interventions in the context of theories of health behaviour change

Abstract: The purpose of this literature review is to determine whether and to what extent current post-fracture osteoporosis interventions utilize theories of health behaviour change and whether those that are theory-based are more successful in producing desired behaviour changes. Studies were identified by applying additional criteria to the final selection stage of a systematic review of non-surgical osteoporosis interventions in the orthopaedic environment. We identified 42 primary studies targeted at patients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…Many interventional studies have shown that enhanced knowledge encourages patients to seek additional information about osteoporosis and leads to lifestyle changes. [50][51][52][53] Studies conducted in the USA and other countries have shown a low level of knowledge about osteoporosis among general groups of women and men and those at increased risk for osteoporosis because of age, having first-degree relatives with osteoporosis or fracture, having a disability, or receiving chemotherapeutic agents or other medications that negatively affect bone density or other risk factors. [54][55][56][57][58][59][60][61][62] Research has shown that although participants may have good knowledge of what osteoporosis is, they generally have a low level of understanding of the role of medication in reducing fracture risk, various concerns about the side effects of medication, poor understanding of the causes of osteoporosis, and uncertainty about how it can be controlled.…”
Section: Enhancing Patients' Knowledgementioning
confidence: 99%
“…Many interventional studies have shown that enhanced knowledge encourages patients to seek additional information about osteoporosis and leads to lifestyle changes. [50][51][52][53] Studies conducted in the USA and other countries have shown a low level of knowledge about osteoporosis among general groups of women and men and those at increased risk for osteoporosis because of age, having first-degree relatives with osteoporosis or fracture, having a disability, or receiving chemotherapeutic agents or other medications that negatively affect bone density or other risk factors. [54][55][56][57][58][59][60][61][62] Research has shown that although participants may have good knowledge of what osteoporosis is, they generally have a low level of understanding of the role of medication in reducing fracture risk, various concerns about the side effects of medication, poor understanding of the causes of osteoporosis, and uncertainty about how it can be controlled.…”
Section: Enhancing Patients' Knowledgementioning
confidence: 99%
“…Osteoporosis is associated with increased morbidity and mortality and decreased quality of life. [1,2] Osteoporosis care reduces risk of future fractures by about 50%. [3,4] Regardless, fewer than 20% of adults, 50 years of age and older, are tested or treated for osteoporosis after a lowtrauma fragility fracture [3,4] generating a substantial and unwarranted "care gap."…”
Section: Introductionmentioning
confidence: 99%
“…Osteoporosis is a chronic condition associated with increased morbidity and mortality and decreased quality of life ( 1 , 2 ). Older adults who suffer from a low trauma (fragility) fracture have a 20% risk of another osteoporosis-related fracture within 1 year ( 1 – 3 ). Fortunately, initiation of bisphosphonate treatment reduces this risk by 50% ( 4 ).…”
Section: Introductionmentioning
confidence: 99%